An institutional analysis of British CVE propaganda policy, 2006-2019 - Porter, David T.B. (2020)
This thesis is an institutionalist examination of the development of British CVE propaganda policy from 2006 to 2019. The central focus of examination is the Research Information and Communications Unit (RICU), established under Gordon Brown in 2007. However, it also investigates the development of associated policy for censorship of extremist material. The driving aim of this analysis is to ascertain how the British state has adapted itself to the newly dominant modes of political and social communication, undergirded by technological advance in terms of hardware, software, platforms and ever-widening participation. Through careful institutionalist observation, the thesis seeks to disentangle this policy evolution to extract and separate intra-governmental and intra-organizational factors from the inescapable demands of a rapidly shifting information economy. Such an operation allows us to make contributions in two complimentary fields. First, it reveals the processes that guide policy evolution in British security matters. Secondly, such a separation allows us to identify the degree to which such changes have been technologically determined – either by facilitating gentle experimentation, or through reversing underlying policy assumptions. In simpler terms, we are not only interested in how the British state has reshaped itself to face the challenges of the internet, but how the internet itself has implacably bent the British state to its own force and logics. Doing so can illuminate many threads relevant to scholarly attention. We can appreciate more fully the process of how new technological realities are negotiated by the British state, the internal policy-making process, and by extension how this process has impacted the political culture of the United Kingdom.